Prevalence of Burnout in Iran: A Systematic Review and Meta-Analysis - Ehsan Bastami; Kourosh Sayehmiri; Tahereh Bastami; Behzad Cheraghizadegan (بهداشت و ایمنی کار, 2020)
Introduction: Burnout dimensions include the emotional exhaustion (EE), depersonalization (DP) and personal accomplishment (PA). Materials and Methods: The information was obtained from searching standard Persian and English keywords in accessible databases including: Scopus, Magiran, SID, Science Direct  and  PubMed from database commencement to April 2017. Data  Analysis was performed using Stata version 11.1., and p value was considered less than 0.05. Results: In the systematic review 43 studies met the inclusion criteria, and 9456 people were evaluated. The prevalence of burnout was calculated in any of the three dimensions of burnout. The prevalence of the Emotional Exhaustion (EE) dimension of burnout was%36 (%95CI: 29-42), the Depersonalization (DP) dimension was%23 (%95CI: 18-29) and the Personal Accomplishment (PA) dimension was%46 (%95CI: 39-53). Based on the type of the job, the maximum prevalence of the EE, DP and PA dimensions was in librarians 67% (%95CI:40-93), university staff 51% (14-88) and dentists 72%(%95CI:65-79), respectively. Meta regression results showed that there was no significant relationship between the year of publication and the prevalence of burnout. Conclusion: According to the prevalence of burnout in Iran and the high prevalence of the PA dimension, it is recommended to consider mediating strategies for reducing and controlling stressful occupational events and burnout in organizational schedule.